Financial Literacy, FinTech, and Contemporary Innovation in Islamic Economic Law: An Analysis of MSME Performance Sustainability in Indonesia and Malaysia - Muhammad Nanang Choiruddin; Heri Pratikto; F. Danardana Murwani; Nurika Restuningdiah (Faculty of Sharia, IAIN Metro, 2025)
This study investigates the relationship between financial literacy, financial technology (FinTech), and contemporary innovation in Islamic economic law and how these factors influence the sustainability of micro, small, and medium enterprises (MSMEs) in Indonesia and Malaysia. Using a qualitative research design, this study gathers and analyses data through comprehensive literature reviews, in-depth interviews with key MSME stakeholders, and targeted surveys involving entrepreneurs within a Sharia-compliant framework. The findings suggest that a high level of financial literacy, effective utilisation of Sharia-based FinTech solutions, and responsiveness to contemporary innovations in Islamic economic law significantly enhance MSMEs' competitiveness and long-term sustainability. These elements facilitate better financial decision-making and operational efficiency and strengthen consumer trust in Sharia-compliant business practices. However, the study also identifies persistent barriers, including uneven financial literacy levels among MSME actors, limited digital infrastructure in rural areas, and insufficient access to appropriate FinTech platforms tailored to Islamic economic values. Furthermore, the research emphasises the critical role of coordinated government policies, institutional support, and multi-stakeholder collaboration in fostering a robust ecosystem that nurtures the growth of Sharia-compliant MSMEs in the digital age. The insights offered by this study contribute meaningfully to the academic discourse on Islamic economics and provide practical recommendations for policymakers, financial institutions, and business practitioners. Ultimately, the research highlights the strategic importance of MSMEs as catalysts for inclusive, ethical, and sustainable economic development in Indonesia and Malaysia.